2019
DOI: 10.1038/s41598-019-38997-7
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling a novel Trichormus variabilis-Synechocystis sp. interaction to boost phycoremediation

Abstract: To conserve freshwater resources, domestic and industrial wastewater is recycled. Algal systems have emerged as an efficient, low-cost option for treatment (phycoremediation) of nutrient-rich wastewater and environmental protection. However, industrial wastewater may contain growth inhibitory compounds precluding algal use in phycoremediation. Therefore, extremophyte strains, which thrive in hostile environments, are sought-after. Here, we isolated such an alga - a strain of Synechocystis sp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Cytoplasmic signalling enables a single cell to initiate signalling and control physiological processes, as demonstrated by some multicellular photosynthetic prokaryotic systems, which can fix nitrogen (N). Nitrogen‐fixing cyanobacteria in the genus Anabaena grow as filaments consisting of chains of pluripotent photosynthetic cells when supplied with sufficient nitrate or ammonium in the growth medium (Abedi et al ., 2019a). Nitrogen limitation activates differentiation of one in every 10–20 photosynthetic cells into thick‐walled heterocysts, which are capable of fixing atmospheric N 2 (Abedi et al ., 2019b).…”
Section: Intercellular Signalling – Where a Single Cell Can Call The ...mentioning
confidence: 99%
“…Cytoplasmic signalling enables a single cell to initiate signalling and control physiological processes, as demonstrated by some multicellular photosynthetic prokaryotic systems, which can fix nitrogen (N). Nitrogen‐fixing cyanobacteria in the genus Anabaena grow as filaments consisting of chains of pluripotent photosynthetic cells when supplied with sufficient nitrate or ammonium in the growth medium (Abedi et al ., 2019a). Nitrogen limitation activates differentiation of one in every 10–20 photosynthetic cells into thick‐walled heterocysts, which are capable of fixing atmospheric N 2 (Abedi et al ., 2019b).…”
Section: Intercellular Signalling – Where a Single Cell Can Call The ...mentioning
confidence: 99%
“…Afterward, three different concentrations, including concentrations less than, as much as, and larger than ED50, were selected to be tested on the microalgae. Accordingly, three concentrations of each considered pharmaceutical, 50, 150, and 250 mg L –1 for ranitidine, 20, 60, and 100 mg L –1 for tramadol, and 100, 150, and 200 mg L –1 for gabapentin, were introduced to the culture medium separately, and their effects on the algal biomass production were monitored daily through OD measurements at 680 nm and compared with the control culture medium, which lacked these drugs 28 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been reported in some studies that it can also be a good candidate for removing pharmaceuticals. [28][29][30] However, no study has thoroughly investigated the ability of Trichormus variabilis to remove or reduce such compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vector graphics were drawn using Inkscape software, v0.92 . To provide images of T. variabilis cells, algal samples were cultivated and processed for transmission electron microscopy (TEM) as described previously . All the tables in this review were constructed from the primary results reported in different studies cited within each table.…”
Section: Methodsmentioning
confidence: 99%